HUBUNGAN PENGETAHUAN DENGAN KEPATUHAN PASIEN TB PARU TERHADAP PENGOBATAN DI RSU BANGKATAN BINJAI - Sri Wahyuni (Jurnal Maternitas Kebidanan, 2020)
Pulmonary tuberculosis is a chronic infectious disease caused by Mycobacterim Tuberculosis. The most important thing that must be considered and done by patients with pulmonary tuberculosis is regularity in taking medication, if this is not done then the previous treatment is in vain, because the germ of pulmonary tuberculosis becomes resistant, making it difficult to treat. This study aims to determine the relationship of knowledge with adherence of pulmonary tuberculosis patients to treatment in Bangkat Binjai General Hospital in 2019. This type of quantitative research uses a correlational descriptive design. The population is all patients in Bangkat Public Hospital, the sample of the study used a total sampling of 30 people, how to collect data using questionnaires as many as 10 questions given to respondents, data processing has been collected, and data analysis is arranged in questions consisting of 10 questions given a score 1 if the answer is true 0 if wrong. The results of this study indicate good knowledge as many as 20 people (66.6%), enough as many as 6 people (20%) and less knowledge as many as 4 people (13.3%), adherence in the category of adherence as many as 21 people (70%) and 9 people did not comply (30%). From the Pearson correlation test results in the Asyim column sig (2-tailed) shows the probability value. The sig value is 0,000 which means that (p <0.05), then h0 is rejected and ha is accepted. There is a significant relationship between knowledge and adherence of pulmonary TB patients with treatment. The better the patient's knowledge of the disease, methods of transmission and treatment of pulmonary TB, the better the adherence they have, and vice versa. It is expected that health workers can collaborate to build good partnerships to provide adequate health education for sufferers, especially related to the importance of adherence in undergoing treatment.